EXACT: A tool for comprehending VBA‐based Excel spreadsheet applications. Issue 6 (28th April 2016) - Amalfitano, Domenico; De Simone, Vincenzo; Fasolino, Anna Rita; Tramontana, Porfirio
Abstract: Spreadsheet applications are widely adopted by millions of end users from several application domains and provide strategic support to many business, scientific, industrial, and organizational processes. These applications are usually developed by rapid application development processes, exploiting host scripting languages allowing the basic spreadsheets to provide complex functionality, business rules, and user interfaces. Several factors complicate the comprehension of these applications because they are usually developed and maintained by end users without specific software engineering skills, grow over time, are not adequately documented, and do not present explicit separation between data, business logic, and user interface layers. This paper presents a reverse engineering tool intended to support the comprehension of Excel spreadsheet applications developed using the Visual Basic for Application programming language. The tool has been implemented as an add‐in that extends the Excel working environment by providing analysis and visualization features. It is able to extract information about the elements composing the analyzed Excel spreadsheet application, the functionality it exposes through its user interface, and the dependencies among its cells. This information is provided by means of interactive views. The validity of the tool has been assessed by a qualitative case study performed with professional end users from an automotive industrial domain. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Excel Application Comprehension Tool is a reverse engineering tool for supporting the comprehension of Visual Basic for Application‐based Excel spreadsheet applications. It implements novel Visual Basic for Application code analysis techniques for recovering the structural elements of the spreadsheet, the functionality it offers through its user interface, and the dependency relationships among its cells. This information is rendered through several interactive views. A qualitative case study performed in an automotive industry showed the usefulness of Excel Application Comprehension Tool in supporting the execution of comprehension tasks carried out in real maintenance projects.